Structural analysis of APOB variants, p.(Arg3527Gln), p.(Arg1164Thr) and p.(Gln4494del), causing Familial Hypercholesterolaemia provides novel insights into variant pathogenicity - Fernández-Higuero, J.A. (2015)
Familial hypercholesterolaemia (FH) is an inherited autosomal dominant disorder resulting from defects in the low-density lipoprotein receptor (LDLR), in the apolipoprotein B (APOB) or in the proprotein convertase subtilisin/kexin type 9 (PCSK9) genes. In the majority of the cases FH is caused by mutations occurring within LDLR, while only few mutations in APOB and PCSK9 have been proved to cause disease. p.(Arg3527Gln) was the first mutation in APOB being identified and characterized. Recently two novel pathogenic APOB variants have been described: p.(Arg1164Thr) and p.(Gln4494del) showing impaired LDLR binding capacity, and diminished LDL uptake. The objective of this work was to analyse the structure of p.(Arg1164Thr) and p.(Gln4494del) variants to gain insight into their pathogenicity. Secondary structure of the human ApoB100 has been investigated by infrared spectroscopy (IR) and LDL particle size both by dynamic light scattering (DLS) and electron microscopy. The results show differences in secondary structure and/or in particle size of p.(Arg1164Thr) and p.(Gln4494del) variants compared with wild type. We conclude that these changes underlie the defective binding and uptake of p.(Arg1164Thr) and p.(Gln4494del) variants. Our study reveals that structural studies on pathogenic variants of APOB may provide very useful information to understand their role in FH disease.